2015
DOI: 10.1083/jcb.201503081
|View full text |Cite
|
Sign up to set email alerts
|

NF2/Merlin mediates contact-dependent inhibition of EGFR mobility and internalization via cortical actomyosin

Abstract: Merlin and Ezrin are central to a mechanism whereby mechanical forces transduced across the apical actomyosin cytoskeleton from cell junctions control the mobility and internalization of EGFR, providing novel insight into how cells inhibit mitogenic signaling in response to cell contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 61 publications
6
58
3
Order By: Relevance
“…Although it has been reported almost 20 years ago that ERBB2 can inhibit the transcription of the E-cadherin gene [22], functional interactions between E-cadherin and ERBB2 or ERBB3 remained largely unexplored. We also did not observe any influence of the ERBB2 or ERBB3 status on the levels of Merlin, another protein known to affect EGFR [23] as well as ERBB2 and ERBB3 [24] in the context of contact-dependent inhibition of proliferation. While EGFR and E-cadherin behaved as expected upon increasing confluence, no noteworthy alteration was observed regarding ERBB2 or ERBB3.…”
Section: Discussioncontrasting
confidence: 48%
“…Although it has been reported almost 20 years ago that ERBB2 can inhibit the transcription of the E-cadherin gene [22], functional interactions between E-cadherin and ERBB2 or ERBB3 remained largely unexplored. We also did not observe any influence of the ERBB2 or ERBB3 status on the levels of Merlin, another protein known to affect EGFR [23] as well as ERBB2 and ERBB3 [24] in the context of contact-dependent inhibition of proliferation. While EGFR and E-cadherin behaved as expected upon increasing confluence, no noteworthy alteration was observed regarding ERBB2 or ERBB3.…”
Section: Discussioncontrasting
confidence: 48%
“…The tumor suppressor Merlin, encoded by the gene neurofibromatosis type 2 (NF2) is responsible for the regulation of EGFR in response to cell contact [108]. The mechanism of this occurrence is not yet understood but it was observed that Merlin binds to EGFR, blocking its internalization and this might immobilize the EGFR on the plasma membrane and stabilize cell junctions [108]. NF2 mutations are found in different pathologies, especially in malignant mesothelioma and Neurofibromatosis type 2.…”
Section: Hallmarking Cancermentioning
confidence: 99%
“…This phenomenon may not be restricted to Drosophila embryos. The increased contractile actomyosin on the apical cortex of human cell lines deficient for the cortex actin regulator Merlin is associated with a condensation of adherens junctions toward the apical surface, suggesting that the response of adherens junctions to cortical tension can be of general significance (Chiasson-MacKenzie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%